Measuring the efficiency of China's carbon market: A comparison between efficient and fractal market hypotheses. (20th October 2020) - Liu, Xianfeng; Zhou, Xinxing; Zhu, Bangzhu; Wang, Ping
Abstract: In this study, variance ratio test and detrended fluctuation analysis are adopted to measure the efficiencies of Beijing, Guangdong, Hubei, Shanghai, Shenzhen, Tianjin and Chongqing seven carbon markets in China. The empirical results indicate that on the basis of efficient market hypothesis, adopts variance ratio test, Hubei and Guangdong markets are weak efficient, Beijing, Shenzhen and Shanghai markets are inefficient, and the efficiencies of Tianjin and Chongqing are uncertain under daily returns. All seven carbon markets are weak efficient under weekly returns. On the basis of fractal market hypothesis, Hurst exponents are obtained by detrended fluctuation analysis, Shanghai, Guangdong and Hubei markets are weak efficient, the other four markets are inefficient under daily returns. Beijing and Hubei markets are weak efficient and the other five markets are inefficient under weekly returns. On the whole, the efficiencies of China's carbon markets are generally low. Combining the empirical results with the reality of China's carbon markets, it's proved that the results of fractal market hypothesis are more convincing. In comparison to efficient market hypothesis, fractal market hypothesis can more effectively measure the efficiency of carbon market. Highlights: Variance ratio test and detrended fluctuation analysis are used to measure the efficiency of carbon market. The efficiencies of China's seven carbon markets are generally low. Compared with efficient market hypothesis, fractal market hypothesis can better measure the efficiency of carbon market.